S132 Investigating the role of Pellino1, an E3 ubiquitin ligase, in modulating signalling pathways controlling the inflammatory response. (2nd December 2011) - Bennett, J A; Prince, L R; Stokes, C A; Parker, L C; Whyte, M K; Sabroe, I
Abstract : Viruses, such as Rhinovirus, are a major cause of asthma exacerbations. Pellino1 was identified as an interleukin 1 receptor associated kinase binding partner and has shown to act as an E3-ubiquitin ligase that is involved in Lysine-63 polyubiquitination of interleukin 1 receptor associated kinase 1/4 and RIP1, which are key mediators of the Toll-like receptor and interleukin 1 receptor (IL-1R) signalling pathways. As such, these pathways are implicated in responses to both bacterial and viral infections. However, the functional importance of Pellino proteins in regulating immune responses and their role in airway inflammatory diseases is yet to be elucidated. We hypothesised that Pellino1 would play a critical role in regulating the inflammatory response in the lung airway epithelium. Pellino1 was knocked down in the human bronchial airway epithelial cell line BEAS2B and primary human bronchial epithelial cells (PBECs) using targeted siRNA. Knockdown of Pellino1 at the transcriptional level was measured using qPCR. Pellino1 knockdown cells were stimulated with Toll-like receptor/IL-1R agonists or the natural pathogen rhinovirus 1B (RV1B) and cytokine release was measured using ELISA. Signalling pathways were explored by western blotting.Pellino1 was expressed in BEAS2B and primary bronchial epithelial cells. Pellino1 mRNA transcript level was knocked down by 78% in BEAS2B and 94% in PBECs. Pellino1 knockdown led to reduced IL-8 generation in response to IL-1ß and a viral mimic Poly (I:C) stimulation in BEAS2B, however RANTES production was unchanged. In contrast to the BEAS2B, the primary bronchial epithelial cells exhibited preserved IL-1 signalling. However, these cells also showed a reduction in IL-8 production in response to both Poly (I:C) stimulation and RV1B infection. Pellino1 knockdown had no effect on the interferon-stimulated gene RANTES production. Pellino1 knockdown leads to reduced IL-8 production in response to a viral mimic Poly (I:C) in lung airway epithelial cells and RV1B in PBECs. These data indicate that Pellino1 regulates proinflammatory responses in airway epithelium and may be a feasible target to downregulate neutrophillic airway inflammation while retaining antiviral immunity, which would be highly beneficial in the treatment of chronic airway inflammatory disorders such as asthma and COPD. These studies were supported by an MRC/Asthma UK PhD studentship.